Integrating Mobile-Assisted Language Learning (MALL) to Explore Papuan Students’ English Learning - Ilal Rizki; Abd. Rahman; Hasbullah Hasbullah (South Sulawesi Education Development (SSED), 2025)
Papuan students often encounter challenges in engaging with English learning due to limited access to conventional resources and low motivation. This raises the need for innovative learning tools that can enhance student engagement and language acquisition. This study aims to examine the level of interest among southwest Papuan students at SMP Negeri 3 Sorong Regency in learning English using Mobile Assisted Language Learning (MALL), identify the types of MALL applied, and evaluate its impact on student learning outcomes. Using a sequential mixed-methods design, data were collected through questionnaires and in-depth interviews with ninth-grade students from SMP Negeri 3 Sorong Regency, southwest Papua. The findings indicate a high level of student interest in learning English through MALL. Frequently used MALL tools included Canva, Google Translate, social media, Brainly, and educational game apps. MALL contributed to increased student motivation, creativity, collaboration, writing ability, and more efficient study time. This research lies in its focus on MALL use among indigenous southwest Papuan students in a rural junior high school context. This study implies that integrating mobile technology can significantly enhance English learning in under-resourced regions like southwest Papua.